Technical Study of the Drainage System Mine Dewatering at the Open Mine at PT Bukit Makmur Istindo Nikeltama - Cahyono, Yudho Dwi Galih; Sari, Avellyn Shinthya; Sikopa, Maudy Cheisylia; Warayaan, Regina (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
The high rainfall that occurred throughout 2024 caused the capacity of the existing sedimentation pond to be unable to accommodate it, resulting in water overflowing and flooding the mining area. This study aims to examine the existing drainage system using quantitative and qualitative research methods. Based on the 2014-2023 rainfall analysis, Log Pearson III distribution with a 5-year return period, the planned rainfall was 142.25 mm/day, Rain Intensity 23.31 mm/hour for a rainfall duration of 3.08 hours/day. The total discharge entering the main sump was 7,771 m3/day and was discharged through the sump outlet mouth, connected by a ditch to Settlingpond 8. At this research location, there were 3 trapezoidal ditches namely: Ditch I 1.78 m3/sec, Ditch II 1.85 m3/sec, Ditch III 2.2 m3/sec. The calculation results showed that the main sump and ditch could still accommodate the total incoming discharge. The capacity of Sedimentation Pond 8, with a volume of 7,025 m3, is not sufficient to accommodate the total inflow of 8,293 m3/second and a sedimentation rate of 40-50%. Considering that the research area cannot be expanded due to land limitations, it is necessary to increase the height by 5 meters in the three settling pond compartments to enhance sedimentation efficiency. In addition, it is necessary to add 1 Ebara 200 x 150 FS4NA pump in the last compartment to help discharge water with a total discharge of 8,293 m3/day. The benefit of this research is that it is able to provide recommendations for managing the mine drainage system.